Pemanfaatan Energi Surya Pada Hidroponik Sebagai Upaya Mendukung Program Pembangunan Berkelanjutan di Kelurahan Ulujami - Akhmad Musafa; Sujono Sujono; Syahrul Awal (Artinara, 2025)
The cultivation of food crops using a hydroponic system represents one of the activities in which the residents are engaged in order to support the sustainable development programme in RW 04, Ulujami sub-district, Pesanggrahan, South Jakarta. However, the pump system's water circulation operation in this hydroponic system still relies on an electrical energy source distributed from a residential property. The primary concern is that this will lead to increased electricity consumption, resulting in a financial burden for these residents. Consequently, the community service activity entailed training on the utilisation of renewable energy sources, namely sunlight, through the implementation of a photovoltaic system as a substitute for conventional energy sources. The objective of this initiative is to facilitate the acquisition of knowledge and skills among partner communities in the utilisation of photovoltaic systems for the domestic fulfilment of electrical energy requirements, thereby enhancing autonomy and reducing reliance on electricity supplied by PLN. The community service activity was meticulously executed in three stages: namely, preparation (comprising a location survey and discussion about partner issues), implementation (involving the design and fabrication of apparatus, socialisation and demonstration of the utilisation of photovoltaic systems as a power supply for hydroponic systems, in addition to monitoring and evaluation), and finalisation. The results of the activities that have been carried out demonstrate the community's enthusiasm for participating in the socialisation process, as it is regarded as a potential solution to the problem of the sustainability of the hydroponic system at partner locations by utilising renewable energy sources.